Development of a novel method to estimate fluid flow rate in oil wells using electrical submersible pump - Ganat, Tarek A.; Hrairi, Meftah; Hawlader, Mohammad Nurul Alam; Osman, Farj (Elsevier, 2015)
The significant challenge in the oil and gas industry is the simultaneous measurement of commingled gas, oil and water streams, using the three phase test separator or multiphase flow meter (MPFM). A major issue in the application of using either test separator or MPFM in oil fields is the uncertainty of the measurements, due to different process and operations conditions. This paper proposes a new computational method to estimate the electrical submersible pump (ESP) oil wells flow rates. The research idea is to close the wellhead wing valve, to measure the wellhead flowing pressure before and after closing the well head valve, and to record the total shut-in time period. Explicit physics concepts for estimations of the multiphase fluid flow rate in a vertical pipe were employed. The formulas deal with changes of fluid flow parameters along the vertical pipe in the well, as a function of pressure and temperature variations with depth. A Microsoft visual basic program was also developed based on the oil mechanistic and empirical equations that can estimate oil rate for ESP oil wells. The new method was applied on 34 ESP oil wells in a North African oil field and lead to very reliable estimation results, which have about a +/-10% relative error, and can be applied to all fluid types and under any production conditions.